Development and testing of an oil palm (Elaeis guineensis Jacq.) fruit digester process for kernel free in crude palm oil production - Wondi, Mohd Hafizz; Haris, Nur Izzah Nabilah; Shamsudin, Rosnah; Yunus, Robiah; Mohd Ali, Maimunah; Iswardi, Aditya Hutama (Elsevier, 2024)
Current palm oil extraction techniques involve the digestion and pressing of entire oil palm fruitlets. However, the coexistence of mesocarp fibre and nut during pressing could inevitably result in oil loss due to fragmentation of the fibre and nut. The anticipated separation of palm mesocarp fibre and kernel prior to pressing is a potential solution to the problem. In order to enhance the extraction of crude palm oil, a digester machine with kernel free has been created. Each machine iteration consists of two processes. The first phase involved severing and removing the mesocarp fibre from the kernel (seed), as well as removing all mesocarp produced by the process, while the second phase involved releasing the nut. The effectiveness of the created machine was evaluated under various conditions, such as speed (700, 900, 1100, 1300, and 1500 rpm) and processing time (20, 30, and 40 s). The optimal condition, which consisted of a rotational speed of 1500 rpm and a separation time of 40 s, was evaluated further under loading weight (2.50, 3.75, and 5.00 kg). The optimal separation was attained with a separation speed of 1100 rpm, a time of 30 s, and a loading mass of 2.50 g, according to the results. Under these conditions, the machine could achieve a separation efficiency of 94.89 and a kernel disintegration rate of 4.29. The investigation's findings benefit the palm oil industry by eliminating processes like winnowing and nut separation through effective implementation of the kernel-free digester machine. © 2023 Elsevier B.V.